DEVELOPMENT OF CLASSIFICATION OF LOOP THREAD TAKE-UP MECHANISMS FOR CHAIN STITCH SEWING MACHINES BASED ON THEIR STRUCTURAL ANALYSIS - МАНОЙЛЕНКО, О. П.; ГОРОБЕЦЬ, В. А.; КНЯЗЄВ, І. М.; ШКВИРА, В. В. (Technologies and Engineering, 2024)
Objective: The purpose of this study is to create a systematized classification of loop take-up mechanisms (LTTU) according to their structural features and to analyze the use of known loop thread feeding mechanisms in sewing machines that implement chain stitches of various types (400, 500, 600 and 800). This analysis will contribute to the establishment of common features and differences in the structure of LTTU for different machine models, which is key for manufacturers and engineers when developing new products. In addition, an important stage is the development of structural diagrams of the mechanisms for feeding loopers in chain stitch sewing machines manufactured by leading companies. This will allow visualization and analysis of the operation of these mechanisms using engineering analysis and determine their impact on the quality and performance of the machine. This approach contributes to the improvement of the quality and efficiency of the use of these sewing machines, which is extremely important in the modern textile industry. The methodology includes the main stages of structural and topological analysis, namely: the formation of functional tasks, the separation of LTTU objects according to principle and functional features into elements (types of cams, links, thread feeders, thread guides, thread tension regulator, the presence of regulation of the law and the amount of thread feeding and etc.), carrying out a topological decomposition of LTTU and establishing relationships between them, without delving into their meaningful description, grouping by type and implementation of the stitch type. Results: A classification of LTTU was developed taking into account their structure and the elements included in them, which can be used at the first stage of designing these mechanisms. The scientific: novelty consists in the structural and topological analysis of LTTU of chain stitch sewing machines and the development of their classification. Analysis of the structure of the LTTU opens up the possibility to identify the elements that are designed to regulate the amount and law of the actual feeding of the thread. This is an important step that expands the range of research objects and leads to scientific improvement in further studies of LTTU. New possibilities of analysis of such elements make it possible to improve the operation of LTTU and optimize the thread feeding process, which is of great importance for increasing the efficiency and reliability of technological processes of chain stitch formation for various chain stitch sewing machines. These scientific results open perspectives for future research and may contribute to the emergence of new innovations in sewing machine engineering. Practical significance: systematization of known LTTU, which facilitates the choice of their structure when designing chain stitch sewing machines of various classes. This classification can be used to take into account various factors when designing LTTU, such as the structure, the principle of operation of the loop thread feeding mechanisms according to the types of stitches. The above diagrams for threading the looper will be useful when threading the threads in chain stitch sewing machines.